Neural architecture : design and artificial intelligence - Campo, Matias del (Novato, CA : Applied Research and Design Publishing, an imprint of ORO Editions, 2022)
This book explores the interdisciplinary project that brings the long tradition of humanistic inquiry in architecture together with cutting-edge research in artificial intelligence. The main goal of Neural Architecture is to understand how to interrogate artificial intelligence - a technological tool - in the field of architectural design, traditionally a practice that combines humanities and visual arts. Matias del Campo, the author of Neural Architecture is currently exploring specific applications of artificial intelligence in contemporary architecture, focusing on their relationship to material and symbolic culture. AI has experienced an explosive growth in recent years in a range of fields including architecture but its implications for the humanistic values that distinguish architecture from technology have yet to be measured. The book illustrates in a series of projects a set of crucial questions for the development of architecture in the future. An opportunity to survey the emerging field of Architecture and Artificial Intelligence, and to reflect on the implications of a world increasingly entangled in questions of the agency, culture and ethics of AI.
ch. I This Building Does Not Exist -- An Attempt at a Theory of Neural Architecture -- What does a Melange have to do with Artificial Intelligence? -- Familiar but Strange: Bits, Pieces, Features & Neurons -- With or Without you -- Dependency between Concrete and Abstract Objects -- Neural Networks are Abstract Objects -- Properties -- It's complicated -- about a Relationship -- About Wild Features and How to Capture Them -- Things, Facts, and the Ontology of Neural Networks -- What About Aesthetics, Agency, and Authorship? -- Aesthetics of Neural Architecture -- The Sensibility of Neural Architecture -- Agency in Neural Architecture -- Neural Architecture is a New Paradigm -- References -- ch. II The Robot Garden -- The Robot Garden -- How to Test a Robot -- Posthuman Design is here -- Big Data, AI and Architecture Design -- References -- ch. III In the Valley of the Hallucinating Machines -- Computational Vision as Design Method -- What Would Turing Do? -- Architecture's Empathy Towards Images and Representation -- How to Recognize a Gothic Column -- The Nature of Neural Networks -- Learning Architectural Features -- Fountains, Figures, and Features -- or How to Confuse an AI -- What it Means to Be a Pixel -- Machines Hallucinating Architecture -- References -- ch. IV Not a Question of Style-Style, Artificial Intelligence and Architecture -- A Closer Look into the Suspicious Noun Style -- When Aesthetics Collide with Technology -- References -- ch. V Talking Architecture -- Talking Architecture -- Materials and Methods -- Initial Modeling -- Attentional Generative Adversarial Network -- The Urban Context of the Design -- Signs, Scripts, and Codes -- A Theory of the Artificial -- References -- ch. VI How Machines Learn to Plan -- A Critical Interrogation of Machine -- Vision Techniques in Architecture -- How machines learn to see -- A Posthuman Trajectory for Plan Formation -- Estranged -- but in a good way -- Neural Networks and Learning the 2-D Visual World -- Modeling the Style of the Real World -- The Defamiliarization of the City, or An Alternative Utopia -- References -- ch. VII Space: The Final Frontier (How to Wrangle a Neural Network to Deal with 3D Models) -- Terms of Engagement: Aesthetics, Agency, Sensibility, and Other Nasty Problems -- Aesthetics -- Sensibility -- Agency -- Authorship -- Database Construction -- Neural Optimization Framework -- Experiments and Results -- So, Can a Neural Network Learn a Sensibility? -- References -- ch. VIII The Politics of Neural Architecture and Artificial Intelligence -- The Problem with Low-Skill Labor -- The Accelerationist Project -- The Return of Ornament -- References.
Includes bibliographical references (pages 212-213) and index.
ARC
Trim Education
Keywords: Architecture and technology; Artificial intelligence -- Industrial applications; Architecture et technologie; Intelligence artificielle -- Applications industrielles; Architecture and technology; Artificial intelligence -- Industrial applications